Effects of different porcine reproductive and respiratory syndrome vaccine regimes on pig immunity status in selected pig farms in Malaysia - Cheah, Zi Herk (2019)
Vaccination is a key component of PRRS disease control strategies. Various types of vaccines, including killed virus (KV) and modified-live virus (MLV) vaccines had been develop for the control of the disease. In Malaysia field condition, the producers adopted different vaccination regime which either breeder vaccination only or whole herd (both breeder and porker herd) vaccination regime. Therefore, the ideal vaccines option (strain or type) and vaccination approach had remained highly debatable in the market. Thus, the objective of this study is to determine the pig immunity status against PRRS in farm by comparing different farms which practicing different vaccination regime or different types of PRRS vaccines in Malaysia farm condition by using PCR and ELISA technique to check on the vertical and horizontal disease transmission and disease pressure in the farm. There are 4 vaccinations regime being include in this study where Farm A only vaccinated Type 2 MLV in breeder herd, Farm B vaccinated both Breeder and porkers with Type 2 MLV, Farm C only vaccinated Type 1 killed vaccine (KV) in Breeder herd and Farm D vaccinated both Breeder and porker with type 1 MLV. All samples collected from all farms were test with both PCR and ELISA. Results showed that whole herd vaccinating MLV approach is a better option for PRRSv control in the farm compare to breeder approach (Chapter 3). In the farm that practiced whole herd vaccination approach, Type 2 MLV showed its benefit in establishing the dominant strain in the farm and able to better control of PRRSv circulation in the farm as compare to Type 1 MLV (Chapter 4). When comparing between Type 2 MLV and Type 1 KV in breeder herd vaccination approach (Chapter 5), the study showed that Type 2 MLV demonstrated its benefit in controlling PRRSv shedding in the herd over Type 1 KV. The conclusion obtain from this research to combat PRRS by strategically practice whole herd vaccination regime (Chapter 3), using the Type 2 (US strain) vaccine strain (Chapter 4) and MLV type vaccine (Chapter 5).